TMEM9‐v‐ATPase Activates Wnt/β‐Catenin Signaling Via APC Lysosomal Degradation for Liver Regeneration and Tumorigenesis. Issue 2 (17th November 2020) - Jung, Youn‐Sang; Stratton, Sabrina A.; Lee, Sung Ho; Kim, Moon‐Jong; Jun, Sohee; Zhang, Jie; Zheng, Biyun; Cervantes, Christopher L.; Cha, Jong‐Ho; Barton, Michelle C.; Park, Jae‐Il
Abstract : Background and Aims: How Wnt signaling is orchestrated in liver regeneration and tumorigenesis remains elusive. Recently, we identified transmembrane protein 9 (TMEM9) as a Wnt signaling amplifier. Approach and Results: TMEM9 facilitates v‐ATPase assembly for vesicular acidification and lysosomal protein degradation. TMEM9 is highly expressed in regenerating liver and hepatocellular carcinoma (HCC) cells. TMEM9 expression is enriched in the hepatocytes around the central vein and acutely induced by injury. In mice, Tmem9 knockout impairs hepatic regeneration with aberrantly increased adenomatosis polyposis coli (Apc) and reduced Wnt signaling. Mechanistically, TMEM9 down‐regulates APC through lysosomal protein degradation through v‐ATPase. In HCC, TMEM9 is overexpressed and necessary to maintain β‐catenin hyperactivation. TMEM9–up‐regulated APC binds to and inhibits nuclear translocation of β‐catenin, independent of HCC‐associated β‐catenin mutations. Pharmacological blockade of TMEM9‐v‐ATPase or lysosomal degradation suppresses Wnt/β‐catenin through APC stabilization and β‐catenin cytosolic retention. Conclusions: Our results reveal that TMEM9 hyperactivates Wnt signaling for liver regeneration and tumorigenesis through lysosomal degradation of APC.